Use of Proton Pump Inhibitors as Adjunct Treatment for Triple-Negative Breast Cancers. An Introductory Study - Wayne Goh; Inna Sleptsova-Freidrich; Nenad Petrovic (Frontiers Media S.A., 2014)
PURPOSE: Triple negative breast cancers (estrogen, progesterone and human epidermal growth factor 2 (HER2) receptor-negative) are among the most aggressive forms of cancers with limited treatment options. Doxorubicin is one of the agents found in many of the current cancer treatment protocols, although its use is limited by dose-dependent cardiotoxicity. This work investigates one of the ways to suppress cancer growth by inhibiting tumor cell ability to remove acid accumulated during its metabolism by proton pump inhibitor esomeprazole (a drug with extensive clinical use) which could serve as an addition to doxorubicin therapy. METHODS: In this work, we have investigated growth suppression of triple-negative breast cancer cells MDA-MB-468 by esomeprazole and doxorubicin by trypan blue exclusion assay. Measurement of acidification of treated cancer cells was performed using intracellular pH-sensitive probe, BCECF-AM. Finally, expression of gastric type proton pump (H+/K+ ATPase, a target for esomeprazole) on MDA-MB-468 cells was detected by immunofluorescence and Western blotting. RESULTS: We have found that esomeprazole suppresses growth of triple-negative breast cancer cell in vitro in a dose-dependent manner through increase in their intracellular acidification. In contrast, esomeprazole did not have significant effect on non-cancerous breast epithelial MCF-10A cells. Esomeprazole increases doxorubicin effects suggesting that dual treatments might be possible. In addition, response of MDA-MB-468 cells to esomeprazole could be mediated by gastric type proton pump (H+/K+ ATPase) in cancer cells contrary to previous beliefs that this proton pump expression is restricted to parietal cells of the stomach epithelia. CONCLUSION: This study provides first evidence that adjunct use of esomeprazole in breast cancer treatment might be a possible to combat adverse effects of doxorubicin and increase its effectiveness.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.